2011
DOI: 10.1111/j.1600-0838.2009.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

New understanding of the complex structure of knee menisci: Implications for injury risk and repair potential for athletes

Abstract: Menisci help maintain the structural integrity of the knee. However, the poor healing potential of the meniscus following a knee injury can not only end a career in sports but lead to osteoarthritis later in life. Complete understanding of meniscal structure is essential for evaluating its risk for injury and subsequent successful repair. This study used novel approaches to elucidate meniscal architecture. The radial and circumferential collagen fibrils in the meniscus were investigated using novel tissue-prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
49
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 21 publications
(28 reference statements)
9
49
0
1
Order By: Relevance
“…Clamped menisci maintained size and shape while developing circumferential fibers throughout the entire meniscus and radial morphologies that varied from the outer to the inner portion of the meniscus, similar to native tissue (Aspden et al, 1985;Kambic and McDevitt, 2005;Petersen and Tillmann, 1998;Rattner et al, 2011;Vanderploeg et al, 2012). This is the first study to our knowledge, to demonstrate development of native-like radial fibers in tissue engineered meniscus.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Clamped menisci maintained size and shape while developing circumferential fibers throughout the entire meniscus and radial morphologies that varied from the outer to the inner portion of the meniscus, similar to native tissue (Aspden et al, 1985;Kambic and McDevitt, 2005;Petersen and Tillmann, 1998;Rattner et al, 2011;Vanderploeg et al, 2012). This is the first study to our knowledge, to demonstrate development of native-like radial fibers in tissue engineered meniscus.…”
Section: Discussionmentioning
confidence: 60%
“…Further, it has been reported native menisci (independent of species, age, or sex) organize fibrils into $ 5-10 μm core bundles which group together to form the larger collagen fibers commonly seen in meniscal sections (Rattner et al, 2011). In this study, the smallest collagen fiber diameter in clamped menisci (found using the entire span of the rotated FFT histogram) increased from 2 μm to 10 μm by 2 weeks of culture, and remained at 10 μm through 8 weeks (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological characterization of RTFs, first detailed by Skaggs, et al , indicate that they are thin and numerous in the anterior region of the meniscus, and posteriorly become thicker and longer, reaching into the inner one third of the tissue [3]. Serial sections of menisci further show that RTFs generate a unique three-dimensional network within the tissue, with RTFs extending into continuous sheets that weave between the circumferential collagen bundles [6,7]. Meniscal specimens that have a greater density of RTFs have higher tensile properties in the radial direction, suggesting that RTFs contribute to the overall mechanical function of the tissue [3].…”
Section: Introductionmentioning
confidence: 99%
“…1) that surrounds and subdivides the circumferential bundles. 8 While the functional importance of this secondary network has not been widely studied, it appears to facilitate rearrangement of the primary collagen bundles under load. 9 This secondary network is a compositionally distinct matrix compartment, containing colocalized collagens I, II, and VI, 10,11 as well as aggrecan and other proteoglycans.…”
mentioning
confidence: 99%